Measuring the Preventive of Drug Dangers in Elementary Schools - Hajrah Hajrah; Elihami Elihami (Universitas Muhammadiyah Enrekang, 2020)
This study aims to describe the effect of information services as a preventive measure against the dangers of drugs in elementary schools in Enrekang Regency, so students understand and can avoid negative things so that students are not easily affected by deviant behavior. In this case elementary school classroom teachers in Enrekang District plays an important role in the responsibility for drug prevention at the school, however all teachers in primary schools in Enrekang Regency have the same responsibility so that students are saved from the language of drugs. One example of the information service that is provided to elementary school students in Enrekang Regency is providing a guidebook on the dangers of drug abuse. Intensive socialization of the dangers of drugs by inviting speakers from business groups, officials or educational institutions who understand the dangers of drug use so that students are more aware of the dangers of drug use. The help book can help students in getting more information about the dangers of drug abuse.